State of the Art Review of the Application of Computational Fluid Dynamics for High Speed Craft - Ahmad, H. A.; Ayob, A. F. (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2017)
Computational Fluid Dynamics (CFD) field of research continues to advance with several new accomplishments, especially in the field of high speed craft design. This paper presents the application of advanced CFD simulations reported in the literatures in terms of software tools available, hull form optimization, resistance, and seakeeping analysis and propulsion system. It aims to review case studies of several methods utilized to conduct operational simulations that result in useful performance prediction of high speed craft. The simulations reviewed in this paper are referring to the research reported in the literatures over the last decade on patrol boats, catamarans, rescue boats and so on. Some notable analysis were discussed, e.g. resistance and seakeeping analysis, propulsion system, hull form optimization and multi physics We conclude that based on the vast resources available in the literature, CFD is one the best tool for designing high speed craft, however such work could be impacted more by its combination with optimization methods.